Le lieutenant Camille Pierre, un passeur des innovations criminalistiques policières dans les pratiques judiciaires des gendarmes à la Belle Époque - Laurent LÓPEZ (Criminocorpus, 2017)
From the 1880s onwards, some new identification processes worked out by Alphonse Bertillon at the Préfecture de Police de Paris (Paris Police Headquarters) have constituted modern and efficient means used by the police criminal investigation department to fight a fast-rising crime rate. One of these processes was the attacker’s physical description, also known as the “speaking portrait” expected to enable the police to perfectly identify someone whose face features would have been carefully described through this very process. Moreover, this process was, unlike any other, taught to the various components of the French police, namely the Paris headquarters police officers, the Sûreté générale officers as well as to the gendarmes and gardes républicains (the Republican Guard). This identification process was enforced in various ways within each institution with unequal results. At odds with what is usually thought of, one of the unexpected effects of the learning and use of the “speaking portrait” was to bring closer police officers and gendarmes.